2019
DOI: 10.56093/ijans.v89i2.87337
|View full text |Cite
|
Sign up to set email alerts
|

Performance evaluation and prediction of first lactation milk yield in Vrindavani cattle

Abstract: The present investigation was carried out using first lactation milk records of 1,084 Vrindavani cows spread over a period of 17 years (2000–2017). The overall performance, effect of non-genetic factors on the first lactation test day (TD) milk yields, age at first calving (AFC), first lactation length (FLL), first lactation peak yield (FLPY), first lactation average daily yield (FLADY), first lactation 305 days milk yield (FL305MY) and first lactation total milk yield (FLTMY) were investigated. The overall … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 10 publications
2
4
0
Order By: Relevance
“…This estimate was higher than the average EBV of 2050.29 kg reported by Singh et al (2020) for the first set of Kankrej bulls. Estimates lower than the average EBV obtained in the present study were also reported by Banik and Gandhi (2010), Raja (2010) and Girimal et al (2022) in Sahiwal cattle and Pandey et al (2013) in Vrindavani cattle. However, the estimate was lower than the value of 2660.70 kg estimated by the BLUP method in Frieswal cattle (Rajeev et al 2021).…”
supporting
confidence: 64%
“…This estimate was higher than the average EBV of 2050.29 kg reported by Singh et al (2020) for the first set of Kankrej bulls. Estimates lower than the average EBV obtained in the present study were also reported by Banik and Gandhi (2010), Raja (2010) and Girimal et al (2022) in Sahiwal cattle and Pandey et al (2013) in Vrindavani cattle. However, the estimate was lower than the value of 2660.70 kg estimated by the BLUP method in Frieswal cattle (Rajeev et al 2021).…”
supporting
confidence: 64%
“…The principal component regression analysis for lifetime milk yield (LTMY4) evolved equation, LTMY4 = 2400.56 ** + 0.698 ** PC could explain 48.8% variation in the estimated values with adjusted R 2 = 48.5%. Khan et al (2013) reported almost similar results in Vrindavani cattle. They evolved an equation for prediction of LTMY up to 4 th lactation using part lactation records up to two lactations and their data set explained 54.46% variation in estimated values with adjusted R 2 = 53.20%.…”
supporting
confidence: 56%
“…Dhara and Chakravarty (1995) compared multiple regression analysis and principal component analysis to predict breeding value of 305 days milk yield and found results of principal component analysis better than multiple regression analysis for prediction. However, Khan et al (2012) formulated the lifetime prediction model using regression analysis based on birth weight, age at first calving (AFC), first service period (FSP), first dry period (FDP), first calving interval (FCI) and first lactation length (FLL) and part lactation records of 100, 170 and 240 days of first lactation, second lactation and their respective total milk yields and explained 40.32% variation in estimated lifetime yields (total of first 4 lactations) in Vrindavani cattle. Bhatacharya and Gandhi (2005) have compared multiple regression analysis and principal component analysis to predict lifetime milk production and found that total variance was lower from the model having PCs as compared to original variables in the regression model.…”
mentioning
confidence: 99%
“…Similarly, specific disease (6%), nutritional and metabolic disease (5.9%), reproductive diseases/calving associated disorders (4.5%), miscellaneous disease (4.4%), parasitic disease (2.8%) and respiratory disease (0.9%) were rather less prevalent. Sakkariya et al (2011) also observed that most prevalent in Vrindavani cattle was digestive cases (49.1%) but it was restricted mostly to very young age group (0-3 months).The higher cases of digestive disorders in the organized farm could be due to variation in the feeding pattern in different seasons along with availability of fodder and concentrate in that particular period of time. All these surgical cases were mostly related to brick on edge floor in the housing system in adult animal sheds and concrete flooring in the calf unit (Das et al 2016).…”
mentioning
confidence: 81%